Membangun VLAN Dalam Jaringan Komputer Pada Laboratorium Informatika UMMU - Muhammad Zakri Nurdin (JAMINFOKOM - Jurnal Manajemen Informatika dan Komputer, 2023)
Virtual Local Area Network (VLAN) is a method that is often used to distribute several different network segments on router devices with limited physical Ethernet interfaces. The purpose of this research is to identify and study client server-based computer networks and to find out how the Virtual Local Area Network works in the application of client server computer networks. IP Address, IP DHCP-Client. then configure Vlan and also Configure Switch Mode Trunk and Access. After that, so that clients can connect with each other, Static Routing must be added to the Router. Routing model uses the route-on-a-stick architecture using trunk and frame and IP techniques from each client will get an IP by DHCP and according to the connected switch. provided the id of the VLAN.